Identifying relevant diabetes and hypertension control management guidelines in primary healthcare and community settings in Indonesia: A Delphi survey. - Eti Poncorini Pamungkasari; Balgis Balgis; Jaap Koot; Jeanet Landsman; Zinzi Pardoel; Martin Rusnak; Dominika Plancikova; Victoria Sari; Stefanus Erdana Putra; Muhammad Hafizhan; Karina Fadillah Ahmad; Lely Pangesti; et al. (PLoS ONE)
The burden of non-communicable diseases (NCDs) in Indonesia is increasing, as evidenced by the latest Indonesian National Health Research, which shows an increase in diabetes prevalence, from 6.9% in 2013 to 10.9% in 2018, and hypertension, from 25.8% in 2013 to 34.1% in 2018. Hence, effective actions in community and primary health care (PHC) facility settings are necessary to tackle the burden of diabetes and hypertension, especially in low- and middle-income countries. The Indonesian government has issued numerous guidelines regarding NCDs. However, not all these guidelines can be applied to communities or PHCs. This study aimed to identify priority guidelines to support the community and PHC for NCD management using the Delphi survey method. These prioritized guidelines will serve as valuable resources for developing relevant, operational and comprehensive modules for community cadres and PHC staff involved in NCD management. The Delphi survey involved 25 experts and comprised three rounds using a questionnaire: 1) identification and assessment of guidelines, 2) assessment of the importance of guidelines, and 3) nomination of the three main priority guidelines. The results revealed three priority guidelines: NCD management guidelines, technical guidelines for Pos Pembinaan Terpadu (POSBINDU) NCDs, and integrated services for NCDs in PHC facilities. Additionally, priority guidelines were used to develop operational modules for community cadres and PHC staff in NCDs management. In conclusion, utilizing the Delphi method serves as a scientific approach to identify priority guidelines crucial for supporting the community and PHC in managing NCDs, particularly in countries with contexts similar to Indonesia.